2002
DOI: 10.1128/jb.184.13.3419-3425.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the PceA Reductive Dehalogenase of Desulfitobacterium sp. Strain Y51

Abstract: The tetrachloroethene (PCE) reductive dehalogenase (encoded by the pceA gene and designated PceA dehalogenase) of Desulfitobacterium sp. strain Y51 was purified and characterized. The expression of the enzyme was highly induced in the presence of PCE and trichloroethene (TCE). The purified enzyme catalyzed the reductive dehalogenation of PCE via TCE to cis-1,2-dichloroethene at a specific activity of 113.6 nmol · min ؊1 · mg of protein ؊1 . The apparent K m values for PCE and TCE were 105.7 and 535.3 M, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 35 publications
6
129
0
1
Order By: Relevance
“…A second deep-branching group of RdhA sequences contains D. restrictus PceA (RdhA24) and two slightly more distant members (RdhA20 and -22). These proteins form a closely related family together with some of the best-characterized enzymes, namely PceA of several Desulfitobacterium hafniense isolates [4,73,74], DcaA of Desulfitobacterium dichloroeliminans [57] and CprA5 (dechlorinating 3,5-dichlorophenol) of Desulfitobacterium hafniense PCP-1 [75]. The last seven RdhA proteins build up a group of highly heterogeneous enzymes for which no characterized counterpart is yet available.…”
Section: Discussionmentioning
confidence: 99%
“…A second deep-branching group of RdhA sequences contains D. restrictus PceA (RdhA24) and two slightly more distant members (RdhA20 and -22). These proteins form a closely related family together with some of the best-characterized enzymes, namely PceA of several Desulfitobacterium hafniense isolates [4,73,74], DcaA of Desulfitobacterium dichloroeliminans [57] and CprA5 (dechlorinating 3,5-dichlorophenol) of Desulfitobacterium hafniense PCP-1 [75]. The last seven RdhA proteins build up a group of highly heterogeneous enzymes for which no characterized counterpart is yet available.…”
Section: Discussionmentioning
confidence: 99%
“…This type of temperature function is well documented for microbial processes (Atlas and Bartha 1987;Empadinhas et al 2004;Suyama et al 2002), and for reductive dechlorination reactions in particular (Kohring et al 1989, Holliger 1993, He 2003, and was observed for ZVI dechlorination processes (section 5.3). Note that the rate of some reactions, such as hydrolysis, may also continue to increase with increasing temperature.…”
Section: Zvi Technologymentioning
confidence: 90%
“…The added value of increasing temperatures may not only enhance dissolution further, but biological reaction rates increase with increasing temperature within a specific range of temperature. Microbial activity is a function of temperature, and for mesophilic microorganisms, which include Dehalococcoides ethenogenes (Empadinhas et al 2004) as well as other dehalogenators (Suyama et al 2002), optimal metabolic rates are typically near 30 to 40°C, which ERH can stimulate (Heath and Truex 1994). Figure 2- In addition, Figure 2-5 illustrates the response of DHC 16S rRNA gene and functional reductase genes tceA, bvcA, and vcrA at Fort Lewis NAPL Area 3 before and during ERH heating.…”
Section: In Situ Bioremediationmentioning
confidence: 99%
“…PceC contains six-transmembrane domains, an FMN binding domain, and a C-terminal polyferredoxin-like domain. It is similar to the membrane-binding transcription regulators [28,60]. More examples for the organization of different RDase gene clusters are presented in [28].…”
Section: Genomic Structure and Transcription Regulation Of Reductive mentioning
confidence: 91%
“…Reductive dechlorination reactions are catalyzed by reductive dehalogenases (RDases) The purified PCE RDase, PceA, has proved to transform PCE and TCE to cDCE [60]. The function of TCE RDase, TceA, in transforming TCE to ethene has also been identified [61].…”
Section: Degradation Enzymesmentioning
confidence: 99%